Advertising Strategies of Hyundai Motors In Indian Market - L. Sudershan Reddy; Ranjith P V; Saili Sabnis; Varsha Ganatra; Kailash Shastry; Anastasya Elviona; Liem Gai Sin; Yaw Nee Chee; Daisy Mui Hung Kee; Chareeya A/P Perak Kerof; Wang Qianya; Wei Jiaze (AIBPM Publisher, 2021)
India’s leading passenger car exporter which is Hyundai Motors India Limited has a market share of India’s total car exports about 26 % in 2019. The term strategy is intended a lot for all business entities in today's competitive marketplace. When a company has a distinctive and distinct benefit, it must be inventive with its marketing strategy. Hyundai has introduced and embraced numerous strategies for securing the overall demand for brand placement. This study attempts to investigate traditional and digital advertising conducted by Hyundai Motors Company which will enhance the success of the company in terms of creating the brand and facilitating user engagement. Close-ended questionnaire is used to collect the data for this study. The data was collected from individuals with different income ranges in India through a non-probability purposive convenience sampling method. The result of this study showed that generation nowadays know more about the products through broadcast advertising such as TV and digital media rather than print media such as newspaper and magazine. Therefore, Hyundai Motors should invest more marketing strategy in broadcast and digital advertising.